2019
DOI: 10.15419/bmrat.v6i11.573
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological correlation of invasive squamous cell carcinoma of uterine cervix: A cross-sectional study

Abstract: Objective: Cervical cancer is a common cancer in females. Clinicopathological features vary and are heterogeneous in different studies. This study was taken up to know the clinicopathological correlation in squamous cell carcinoma (SCC) of the cervix in our population. Methods: This is a cross-section study. Histologically confirmed cases of squamous cell carcinoma of the cervix are considered. Clinical history, socio-demographic details, clinical findings including stage and histological grade of the disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Jain et al and Patil et al also showed similar findings as the present study except for irregular bleeding being a more common presentation than the present study. 2,12 The most frequent finding was growth, as reported by Raju et al (65.3%) followed by bleeding and erosion. Similar findings were seen in the present study with growth in 66.2% cases.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Jain et al and Patil et al also showed similar findings as the present study except for irregular bleeding being a more common presentation than the present study. 2,12 The most frequent finding was growth, as reported by Raju et al (65.3%) followed by bleeding and erosion. Similar findings were seen in the present study with growth in 66.2% cases.…”
Section: Discussionmentioning
confidence: 83%
“…Similar age distribution was also seen in the present study. 2,12 Most of the time, early cervical cancer has no symptoms. Vaginal bleeding, postcoital bleeding, or discharge may be the presenting features.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations